Determinants of sexual and reproductive health concerns among youngsters in Albania during COVID-19 pandemic - Gjebrea, Elona; Mali, Juna; Hoxha, Livia (Intelektual Pustaka Media Utama, 2024)
The COVID-19 pandemic has affected all communities, including youngsters. Our aim was to assess the key sexual and reproductive health (SRH) concerns of young people in Albania during the pandemic as well as the factors associated with the main health concern. A cross-sectional study was carried out in Albania in 2021. Multivariable logistic regression analysis was used to assess the association of being concerned about mental health & psychological well-being, urgency for mental health information, and difficulty in getting mental health information with independent variables. In total 340 youngsters aged 14-30 years participated (66% female, 89% Albanian ethnicity, about 20% belonging to the LGBT community). Mental health & psychological well-being were the main SRH topics youngsters were concerned about, reported by 48% of them. About 37% of youngsters had an urgent need for mental health information during the pandemic and 18% experienced difficulty in getting this information. Being part of the LGBT community was associated with a significantly higher likelihood of being concerned about mental health (OR=3.15;95%CI:1.36-7.33), being in urgent need of mental health information (OR=3.68;95%, CI:1.63-8.32) and experiencing difficulties in getting mental health information (OR=3.48;95% CI:1.49-8.13). Higher household income levels also increased the likelihood of being concerned about mental health (OR=4.28;95%CI:1.55-11.77) and being in urgent need of mental health information (OR=4.15;95%CI:1.43- 12.01). In conclusion, young people in Albania have been concerned about various SRH topics during the COVID-19 pandemic, but the major concern was mental health & psychological well-being, especially for the LGBT community. The findings should guide future interventions for addressing youth mental health concerns in emergency situation.